CAADP at 10 - Water is a Missing Link in the Southern African Development Community - Sullivan, Amy; Mashingaidze, Ian (GREAT Insights, 2013)
Water has a low profile in Comprehensive Africa Agriculture Development Programme (CAADP) processes in the Southern African Development Community (SADC), presenting an opportunity to develop stronger ties between the agriculture and water sectors in the region.